Effects of a 110 kilometers ultra-marathon race on plasma hormone levels - Fournier, P. E.; Stalder, J.; Mermillod, B.; Chantraine, A. (International Journal of Sports Medicine, 1997)
To assess changes of sex hormones, cortisol, prolactin (PRL) and beta-endorphins in an exhaustive aerobic performance, blood samples were taken in 11 endurance trained runners (R) along an ultra-marathon race of 110 km (T1 before the start, T2 at km 33, T3 at km 75 and T4 immediately after completing the race). Results were compared to a control group (C) who followed the race. Cortisol (p < 0.001) and beta-endorphins (p = 0.009) showed a significant increase during the race without significant modification after T2. Testosterone decreased along the race (p = 0.02). Luteinising hormone (LH) was lower at the end of the race as compared to the start in the R. No modification of PRL was noticed in the runners. Most of the modifications except for testosterone were observed from the start to T2, even in exhaustive performance no further modification was noticed from that point onwards.